2018
DOI: 10.1016/j.anthro.2018.03.003
|View full text |Cite
|
Sign up to set email alerts
|

The Iron Gates Mesolithic – a brief review of recent developments

Abstract: présente une concentration unique de sites mésolithiques et néolithiques anciens couvrant la période allant d'environ 12.700 à 5600 cal BC. Plus de 50 grottes et sites de plein air ont été identifiés lors de prospections-inventaires archéologiques réalisés avant la construction du barrage dans les années 1960 et 1980, et les fouilles de sauvetage qui ont suivi ont révélé de nombreuse sépultures et vestiges architecturaux, d'importantes quantités de restes fauniques et des objets mobiliers, y compris des oeuvre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…[25,26,32,39,72,79–82]). While at sites such as Schela Cladovei, there is a hiatus between the Late Mesolithic occupation and re-occupation by groups displaying characteristically Neolithic traits [24], recent studies of both ancient DNA and strontium isotope signatures from human tooth enamel now provide evidence for the interaction of immigrant farmers with local foraging communities, including burial of non-locals in a ‘Mesolithic’ tradition [37,38,83,84], leading some authors to recognize a ‘transformational’ phase between the Late Mesolithic and Early Neolithic [26,72]. Our research has demonstrated the continued preparation of riverine resources in the Iron Gates, now using Neolithic pottery, which may relate to both the resource base encountered and cultural interactions occurring within pre-existing and newly formed social networks.…”
Section: Resultsmentioning
confidence: 99%
“…[25,26,32,39,72,79–82]). While at sites such as Schela Cladovei, there is a hiatus between the Late Mesolithic occupation and re-occupation by groups displaying characteristically Neolithic traits [24], recent studies of both ancient DNA and strontium isotope signatures from human tooth enamel now provide evidence for the interaction of immigrant farmers with local foraging communities, including burial of non-locals in a ‘Mesolithic’ tradition [37,38,83,84], leading some authors to recognize a ‘transformational’ phase between the Late Mesolithic and Early Neolithic [26,72]. Our research has demonstrated the continued preparation of riverine resources in the Iron Gates, now using Neolithic pottery, which may relate to both the resource base encountered and cultural interactions occurring within pre-existing and newly formed social networks.…”
Section: Resultsmentioning
confidence: 99%
“…The hybrid character of the site is generally well accepted, with the forager culture seen as “dominant” during the transitional phase (Borić, 2019, p. 43). Assuming that burial in extended supine position parallel to the Danube with the head pointing downstream was the norm among Late Mesolithic Iron Gates HGs (Bonsall & Boroneanț, 2018), then some of the incoming Aegeans can be considered to be buried in a similar fashion to local people during the transitional phase (e.g. Burials 61, 54e).…”
Section: Discussionmentioning
confidence: 99%
“…The hybrid character of the site is generally well accepted, with the forager culture seen as 'dominant' during the transitional phase (Borić, 2019, p. 43). Assuming that burial in extended supine position parallel to the Danube with the head pointing downstream was the norm among Late Mesolithic Iron Gates HGs (Bonsall & Boroneanț, 2018), then some of the incoming Aegeans can be considered to be buried in a similar fashion to local people during the transitional phase (e.g. Burials 61, 54e).…”
Section: Trapezoidal Houses At Lepenski Vir Associated With Incoming ...mentioning
confidence: 99%